Construction of rice chromosome segment substitution lines harboring Oryza barthii genome and evaluation of yield-related traits - Bessho-Uehara, Kanako (Breed Sci, 2017)
Rice (Oryza sativa L.) is one of the most important staple food in the world. To meet the increasing demand for food, a strategy for improving rice yield is needed. Alleles of wild relatives are useful because they confer adaptation to plants under diverse harsh environments and have the potential to improve rice. O. barthii is a wild rice species endemic to Africa and the known progenitor of the African cultivated rice, O. glaberrima. To explore the genetic potential of the O. barthii as a genetic resource, 40 chromosome segment substitution lines (CSSL) of O. barthii in the background of the elite japonica cultivar Koshihikari were developed and evaluated to identify QTLs associated with 10 traits related to flag leaf morphology, grain yield and other agronomic traits. More than 90% of the entire genome of the donor parent was represented in contiguous or overlapping chromosome segments in the CSSLs. Evaluation of the CSSLs for several agriculturally important traits identified candidate chromosome segments that harbors QTLs associated with yield and yield-related traits. These results suggest that alleles from O. barthii might be used as a novel genetic resource for improving the yield-related traits in cultivars of O. sativa.